Penerapan Unplugged Coding untuk Meningkatkan Kemampuan Berpikir Komputasional Peserta Didik Sekolah Dasar di SD Al Hilaal 5 Kranjang - Sriwahyuni, Eka; Talakua, Melvie; Siregar, Hiba Dertyana; Sofyan, Abdul; Pelamonia, Johanes; Detek, Ilin; Jaliy, Suriba Ode (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity was conducted at SD Al Hilaal 5 Kranjang to address limited technological facilities and students’ lack of experience in logical and systematic thinking activities. As a solution, the service team implemented the unplugged coding method, which introduces programming concepts without using computers through paper-based activities that are appropriate for the characteristics of elementary school students. The program was carried out over two days and involved 151 students from grades 1 to 6. The first day focused on students in grades 1–3 through basic logic activities, sequential instructions, and simple patterns. The second day was intended for students in grades 4–6 through a color multiplication coding activity. The implementation methods included socialization, training, technology application, mentoring, evaluation, and program sustainability. The results showed an improvement in students’ computational thinking skills across all assessed aspects. The highest increase was found in basic logical understanding, reaching 27%. These findings indicate that unplugged coding is effective, contextual, and sustainable for elementary school students.